In-vivo 31P-MRS of skeletal muscle and liver: A way for non-invasive assessment of their metabolism - Valkovič, L; Chmelík, M; Krššák, M (Elsevier, 2017)
In addition to direct assessment of high energy phosphorus containing metabolite content within tissues, phosphorus magnetic resonance spectroscopy (31P-MRS) provides options to measure phospholipid metabolites and cellular pH, as well as the kinetics of chemical reactions of energy metabolism in vivo. Even though the great potential of 31P-MR was recognized over 30 years ago, modern MR systems, as well as new, dedicated hardware and measurement techniques provide further opportunities for research of human biochemistry. This paper presents a methodological overview of the 31P-MR techniques that can be used for basic, physiological, or clinical research of human skeletal muscle and liver in vivo. Practical issues of 31P-MRS experiments and examples of potential applications are also provided. As signal localization is essential for liver 31P-MRS and is important for dynamic muscle examinations as well, typical localization strategies for 31P-MR are also described.